Supply Chain Management Ethical Practices and Sustainable Performance of Public Procurement in Lake Region Economic Block, Kenya - Kipkorir, Geoffrey; Chege, Dennis; Kamau, Denis; Ndolo, Jackson (International Journal of Supply Chain and Logistics, 2026)
Purpose: The objective of the study was to supply chain management ethical practices on sustainable performance of public procurement in Lake Region Economic Bloc, Kenya. The focus was on the achievement of economic, social and environmental performance metrics across County and National government departments and agencies. Methodology: Descriptive research design was adopted. The Lake Region Economic Bloc (LREB) that covers 11 counties was used as the focus area of the study. County departments, National government departments and agencies were the targets of the study. A total of 290 officers who are in charge of evaluation of bids, contract administration and users were selected for the sample frame. The researcher therefore distributed 290 questionnaires. Descriptive statistics were developed to facilitate the generation of inferential statistics by use of both univariate and multi-vicariate analysis. Findings: Based on the findings, the study concluded that supply chain management ethical practices positively and significantly influences sustainable public procurement in Kenya. This study therefore recommends that public procurement in Kenya should establish and enforce clear ethical sourcing guidelines and standards. Unique Contribution to Theory, Policy and Practice: This study makes a significant contribution to theory, policy, and practice by demonstrating that ethical supply chain management practices are critical drivers of sustainable public procurement performance. Theoretically, it advances existing knowledge by linking ethical practices with economic, social, and environmental outcomes in procurement systems. From a policy perspective, it provides evidence to support the development and enforcement of stronger regulatory frameworks and ethical standards across public institutions. Practically, the study offers actionable insights for procurement professionals, emphasizing the need for clear ethical guidelines, supplier accountability, and continuous capacity building to enhance efficiency, transparency, and long-term sustainability in public procurement.